Therapeutic potential of Syzygium cumini L. extract in treating anxiety in adult zebrafish (Danio rerio): Behavioral, toxicological, and molecular evidence involving the GABAergic and serotonergic pathways - Cássia Taiane Viana Moraes; Gabriel Martins de Araújo Sousa; Ariel Falanga de Oliveira; Igor de Codes Soares; Paula Ticiani Alves de Souza; Lucca Moura de Freitas; Mário Guilherme de Paula Sales; Vitória Isabele Gomes Ferreira; Paula Alexandre de Freitas; Saulo Chaves Magalhães; Katarine Ferreira da Silva; Luís Sérgio Fonteles Duarte; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Evaluation of web post-buckling in high-strength cellular steel and high-strength concrete composite beams: A numerical study - Jonas Yoshihiro Namba; Igor Eduardo da Silva Ribeiro; Haron Cesar Almeida Tavares; Alexandre Rossi; Pablo Augusto Krahl; Carlos Alberto Benedetty Torres; Carlos Humberto Martins (Engineering Structures, 2025)

Low carbon footprint of Nile tilapia farming with recirculation aquaculture - Anderson M. de Melo Júnior; Sarian Kosten; Vitor Luis da C. Duque; Alexandre A.O. Santos; André M. Amado; Laís C. Soranço; Jochem Dreise; Arthur C. Martins; Jonas Nasário; Ana Paula Dalbem Barbosa; Ive S. Muzitano; Giovana M. Cardoso; et al. (Resources, Conservation and Recycling, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Effects of wind turbine dimensions on the collision risk of raptors: A simulation approach based on flight height distributions - Tonio Schaub; Raymond H.G. Klaassen; Caroline De Zutter; Pascal Albert; Olivier Bedotti; Jean-Luc Bourrioux; Ralph Buij; Joël Chadœuf; Celia Grande; Hubertus Illner; Jérôme Isambert; Kjell Janssens; et al. (Science of The Total Environment, 2024)

Variability of the equatorial ionization anomaly over the South American sector: Effects of electric field and effective meridional wind - Solomon Otoo Lomotey; Jonas Rodrigues de Souza; Cristiano Max Wrasse; Hisao Takahashi; Diego Barros; Cosme Alexandre Oliveira Barros Figueiredo; José Humberto Andrade Sobral; Fábio Egito; Patrick Essien; Toyese Tunde Ayorinde; Anderson Vestena Bilibio; Nana Ama Browne Klutse (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Postural adjustments and perceptual responses of Nordic running: concurrent effects of poles and irregular terrain - André Ivaniski-Mello; Diana Maria Cubillos-Arcila; Stefano Dell’Anna; Lucas de Liz Alves; Flávia Gomes Martinez; Cosme Franklim Buzzachera; Jonas Alex Morales Saute; Leonardo Alexandre Peyré-Tartaruga (European Journal of Applied Physiology, 2024)
Purpose In the natural environment, humans must continuously negotiate irregular and unpredictable terrain. Recently, the poles have been extensively used during trial running events. However, we know little about how humans adjust posture and bilateral coordination to use poles in irregular terrain. Here, we compared kinematics, bilateral coordination and perceptual responses between regular (compact dust) and irregular terrain (medium-length grass) during running at preferred speed with and without poles. Methods In this transversal observational study, thirteen young healthy adults (8 men; mean ± SD; age 29.1 ± 8.0 years, body mass 76.8 ± 11.4 kg; height 1.75 ± 0.08 m) were evaluated during running at a self-selected comfortable speed with and without poles on regular and irregular terrains. Results Our results show that, despite more flexed pattern on lower-limb joints at irregular terrain, the usage of poles was not enough to re-stabilize the bilateral coordination. Also, the perceived exertion was impaired adding poles to running, probably due to more complex movement pattern using poles in comparison to free running, and the invariance in the bilateral coordination. Conclusion Besides the invariability of usage poles on bilateral coordination and lower-limb kinematics, the runners seem to prioritize postural stability over lower limb stiffness when running in medium-length grass given the larger range of ankle and knee motion observed in irregular terrain. Further investigations at rougher/hilly terrains will likely provide additional insights into the neuromotor control strategies used to maintain the stability and on perceptual responses using poles during running.

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Marine teleost fishes of the northeastern Brazilian coast: 166 years of compiled data - Ricardo S. Rosa; Aline P. M. Medeiros; Antônio Felinto; Camila Brito; Erika F. C. Santana; Fernanda V. Albuquerque; Jonas A. Santos; Júlio Lustosa; Katherine M. P. Viana; Marianna B. Silva; Rafael Menezes; Viviana Márquez Velásquez; et al. (Systematics and Biodiversity, 2023)

Characterization and photocatalytic performance of cement mortars with incorporation of TiO2 and mineral admixtures - Rancés Castillo Lara; Gustavo de Castro Xavier; Maria C. Canela; Juliana Alves Carvalho; Jonas Alexandre; Afonso Rangel Garcez de Azevedo (Environmental Science and Pollution Research, 2023)

Static Balance in Hereditary Spastic Paraplegias: a Cross-sectional Study - Diana Maria Cubillos-Arcila; Valéria Feijó Martins; Ana Paula Janner Zanardi; Gustavo Dariva Machado; Daniela Burguêz; Natalia Andrea Gomeñuka; Leonardo Alexandre Peyré-Tartaruga; Jonas Alex Morales Saute (The Cerebellum, 2023)

Eco-friendly ceramic bricks: a comparative study of life cycle impact methods - Josinaldo Dias; Gustavo Xavier; Afonso Azevedo; Jonas Alexandre; Henry Colorado; Carlos Maurício Vieira (Environmental Science and Pollution Research, 2022)

Progression of Functional Gait in Hereditary Spastic Paraplegias - Diana Maria Cubillos-Arcila; Gustavo Dariva Machado; Lauren Sehnem; Daniela Burguêz; Ana Paula Janner Zanardi; Valéria Feijó Martins; Leonardo Alexandre Peyré-Tartaruga; Jonas Alex Morales Saute (The Cerebellum, 2022)

Optical Detection of Harmful Algal Blooms in the Belgian Coastal Zone: A Cautionary Tale of Chlorophyll c3 - Alexandre Castagna; Heidi Dierssen; Emanuele Organelli; Margarita Bogorad; Jonas Mortelmans; Wim Vyverman; Koen Sabbe (Frontiers in Marine Science, 2021)
Phaeocystis globosa is a nuisance haptophyte species that forms annual blooms in the southern North Sea and other coastal waters. At high biomass concentration, these are considered harmful algal blooms due to their deleterious impact on the local ecosystems and economy, and are considered an indicator for eutrophication. In the last two decades, methods have been developed for the optical detection and quantification of these blooms, with potential applications for autonomous in situ or remote observations. However, recent experimental evidence suggests that the interpretation of the optical signal and its exclusive association with P. globosa may not be accurate. In the North Sea, blooms of P. globosa are synchronous with those of the diatom Pseudo-nitzschia delicatissima , another harmful bloom-forming species with similar pigmentation and optical signature. Here we combine new and published measurements of pigmentation composition and inherent optical properties from pure cultures of several algal and cyanobacterial groups, together with environmental spectroscopy data, to identify the pigments generating the optical signals captured by two established algorithms. We further evaluate the association of those pigments and optical signals with P. globosa . We found that the interpretation of the pigment(s) generating the optical signals were incorrect and that previous methods are not specific to P. globosa , even in the context of the phytoplankton assemblage of the southern North Sea. Additionally, we found that the optical and pigment signatures of Phaeocystis species are part of a broad pigmentation trend across unrelated taxonomic groups related to chlorophyll c 3 presence, with important consequences for the interpretation of pigment and optical data. We then develop and evaluate an algorithm to detect this pigmentation pattern with minimal influence of co-occurring species and elaborate general recommendations for the future development of algorithms.

Endocannabinoid System Attenuates Oxaliplatin-Induced Peripheral Sensory Neuropathy Through the Activation of CB1 Receptors - Anamaria Falcão Pereira; Mario Roberto Pontes Lisboa; Bruno Wesley de Freitas Alves; Cristiane Maria Pereira da Silva; Diego Bernarde Souza Dias; Karoline Luanne Santos de Menezes; Francisco Rafael Alves Santana Cesário; Jonas Costa de França; Amanda Rocha de Oliveira; Jaime Eduardo Cecilio Hallak; Antonio Waldo Zuardi; José Alexandre Crippa; et al. (Neurotoxicity Research, 2021)

Occurrence but not intensity of mortality rises towards the climatic trailing edge of tree species ranges in European forests - Alexandre Changenet; Paloma Ruiz‐Benito; Sophia Ratcliffe; Thibaut Fréjaville; Juliette Archambeau; Annabel J. Porte; Miguel A. Zavala; Jonas Dahlgren; Aleksi Lehtonen; Marta Benito Garzón (Global Ecology and Biogeography, 2021)
Aim Tree mortality is increasing world‐wide, leading to changes in forest composition and altering global biodiversity. Nonetheless, owing to the multifaceted stochastic nature of tree mortality, large‐scale spatial patterns of mortality across species ranges and their underlying drivers remain difficult to understand. Our main goal was to describe the geographical patterns and drivers of the occurrence of mortality (presence of a mortality event) and the intensity of tree mortality (amount of mortality related to that mortality event) in Europe. We hypothesized that the occurrence of mortality represents background mortality and is higher in the margin than in core populations, whereas the intensity of mortality could have a more even distribution according to the spatial and temporal stochasticity of die‐off events. Location Europe (Spain, France, Germany, Belgium, Sweden and Finland). Major taxa studied More than 1.5 million trees belonging to 20 major forest tree species. Methods We developed binomial and truncated negative binomial models to tease apart the occurrence and intensity of tree mortality in National Forest Inventory plots at the range‐wide scale. The occurrence of mortality indicated that at least one tree had died in the plot, whereas the intensity of mortality referred to the number of dead trees per plot. Results The highest occurrence of mortality was found in peripheral regions and the climatic trailing edge linked with drought, whereas the intensity of mortality was driven by competition, drought and high temperatures and was scattered uniformly across species ranges. Main conclusions We show that tree background mortality, but not die‐off, is generally higher in the trailing‐edge populations. It remains to be explored whether other demographic traits, such as growth, reproduction and regeneration, also decrease at the trailing edge of European tree populations.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Characterisation of phenolic compounds of the ethyl acetate fraction from Tabernaemontana catharinensis and its potential antidepressant-like effect - Nathielli Nayara Pauleti; Jonas Mello; Diogo Alexandre Siebert; Gustavo Amadeu Micke; Cláudia Almeida Coelho de Albuquerque; Michele Debiasi Alberton; Sara Cristiane Barauna (Natural Product Research, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Starch levels on performance, milk composition and energy balance of lactating dairy cows - Carolina Almeida Carmo; Fernanda Batistel; Jonas de Souza; Junio Cesar Martinez; Paulo Correa; Alexandre Mendonça Pedroso; Flávio Augusto Portela Santos (Tropical Animal Health and Production, 2015)

Assessment of 3D Spatial Interpolation Methods for Study of the Marine Pelagic Environment - Jonas Sahlin; Mir Abolfazl Mostafavi; Alexandre Forest; Marcel Babin (Marine Geodesy, 2014)

Native forest management in subtropical South America: long-term effects of logging and multiple-use on forest structure and diversity - Alexandre F. Souza; Liseane Santos Rocha Cortez; Solon Jonas Longhi (Biodiversity and Conservation, 2012)

Influence of storm damage on the runoff generation in two sub-catchments of the Sperbelgraben, Swiss Emmental - Alexandre Badoux; Michel Jeisy; Hans Kienholz; Peter Lüscher; Rolf Weingartner; Jonas Witzig; Christoph Hegg (European Journal of Forest Research, 2006)